A study on understanding of Malaysian democracy based on demographic factors namely gender, job sectors and race / Awang Nasfuddin Awang Hassan and Abang Ibrahim Abg Sharbini - Awang Hassan, Awang Nasfuddin; Abg Sharbini, Abang Ibrahim (2011)
Election is an important aspect in a country which practices the system of democracy, like Malaysia (Rashidah Abd Ghani, 2008). Since gaining independence five decades ago, world leaders have sung praises of Malaysia's ability to sustain democracy through fair elections. Such praise, coupled with congratulatory messages which Malaysia normally receives after every general election, reflects the confidence of the world leaders in its election system. Therefore, this trust has shown that other nations acknowledge the practice of democracy in Malaysia that has been symbolized by fair and just election process.